Arterial stiffness induced by carotid calcification leads to cerebral gliosis mediated by oxidative stress. Issue 2 (February 2018) - Sadekova, Nataliya; Iulita, M. Florencia; Vallerand, Diane; Muhire, Gervais; Bourmoum, Mohamed; Claing, Audrey; Girouard, Hélène
Abstract : Background: Arterial stiffness is a risk factor for cognitive decline and dementia. However, its precise effects on the brain remain unexplored. Using a mouse model of carotid stiffness, we investigated its effect on glial activation and oxidative stress. Methods: Arterial stiffness was induced by the application of calcium chloride to the adventitial region of the right carotid. Superoxide anion production, NADPH activity and levels, as well as glial activation were examined with immunohistochemical and biochemical approaches, 2-week postcalcification. Antioxidant treatment was done with Tempol (1 mmol/l) administered in the drinking water during 2 weeks. Results: The current study revealed that arterial stiffness increases the levels of the microglial markers ionized calcium-binding adapter molecule 1 and cluster of differentiation 68 in hippocampus, and of the astrocyte marker, s100 calcium binding protein β in hippocampus and frontal cortex. The cerebral inflammatory effects of arterial stiffness were specific to the brain and not due to systemic inflammation. Treatment with Tempol prevented the increase in superoxide anion in mice with carotid stiffness and attenuated the activation of microglia and astrocytes in the hippocampus. To determine whether the increased oxidative stress derives from NADPH oxidase, superoxide anion production was assessed by incubating brain tissue in the presence of gp91ds-tat, a selective NADPH oxidase 2 inhibitor. This peptide inhibited superoxide anion production to a greater extent in the brains of mice with carotid calcification compared with controls. Conclusion: Carotid calcification leads to cerebral gliosis mediated by oxidative stress. Correcting arterial stiffness could offer a novel paradigm to protect the brain in populations where stiffness is prominent. Abstract : Supplemental Digital Content is available in the text